1972
DOI: 10.1104/pp.49.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Induced Changes in Permeability of Plant Cell Membranes to Water

Abstract: The half-time for THO equilibration was three times longer for a living carrot (Daucus carota L.) cylinder than for a dead one. Furthermore, the energy of activation of THO flux was more than twice as high for the living cylinder. Passage through living membranes thus constitutes a rate-limiting step for THO flux in carrot tissue.CO2 increased the half-time (t1/2) for THO equilibration.Treatment with abscisic acid or with tertiary butanol decreased t1/2. In neither case was the selective permeability of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Table V shows the diffusion resistance for four of the alcohols after 3 days in the dark. In addition, Table VI (2).…”
Section: Resultsmentioning
confidence: 99%
“…Table V shows the diffusion resistance for four of the alcohols after 3 days in the dark. In addition, Table VI (2).…”
Section: Resultsmentioning
confidence: 99%
“…9). The exudate from the cold-grown plants was much more dilute in the 10 than the 25 C series. This difference was most dramatic at the lower pressures, and was apparent though not significant at the higher pressures.…”
mentioning
confidence: 97%
“…Such changes alter membrane permeability and enzyme activity (8,10,19). Arrhenius plots were used by Clarkson (2) to study exudation rates and ion concentration of the xylem exudate from excised barley and rye roots preconditioned at various temperatures.…”
mentioning
confidence: 99%
“…Cram and Pitman (3) reported that ABA did not change the hydraulic conductivity of maize or barley roots, but Glinka and Reinhold (9,10) reported that ABA increased both the diffusional permeability and hydraulic conductivity of roots to water flow under a pressure of 0.8 bar. Most recently, ABA was reported to have no effect on osmotically driven water flow in excised sunflower roots (4).…”
mentioning
confidence: 99%